Early post-treatment choroidal thickness to alert sunset glow fundus in patients with Vogt-Koyanagi-Harada disease treated with systemic corticosteroids - Hirooka, Kiriko (PLoS One, 2017)
PURPOSE: To determine if early post-treatment central choroidal thickness (CCT) changes can predict sunset glow fundus (SGF) development in patients with Vogt-Koyanagi-Harada (VKH) disease treated using systemic corticosteroids. METHODS: This retrospective case series included 39 eyes of 21 treatment-naïve patients with acute VKH disease who could be followed up for more than 12 months after systemic corticosteroid therapy. The eyes were divided into two groups according to whether SGF was present or absent at 12 months (9 eyes of 5 patients versus 30 eyes of 16 patients, respectively). Using enhanced depth imaging optical coherence tomography, CCT values were measured before treatment, then at 1 week and 1 and 3 months after treatment in both groups and compared between the two groups. RESULTS: Development of SGF was found 4–11 months after treatment. Mean post-treatment CCT decreased significantly at all examinations compared with baseline in both groups, along with resolution of serous retinal detachment. One week after treatment, mean CCT was significantly higher in eyes with SGF than in those without (P = 0.024). SGF was present at 12 months in 9 of 22 eyes with CCT values > 410 μm at 1 week after starting treatment, in contrast with none of 17 eyes with CCT ≤ 410 μm at this time (P = 0.003). CONCLUSIONS: The current study suggested the potential validity of early post-treatment CCT as a feasible index to alert future progression to SGF in patients with VKH disease treated using systemic corticosteroids.